RD Trainees Teaching MD Trainees: Nutrition Assessment Training for Medical Students. (29th May 2020) - Wickman, Brooke; Ratner, Edward
Abstract: Objectives: Less than 25% of medical schools meet US National Academy of Sciences recommendations to provide 25 hours of nutrition education. Medical trainees report dissatisfaction with nutrition training and unpreparedness to counsel patients about nutrition. A pilot program aims to promote medical student understanding of nutrition and increase confidence in future practice. Obstacles to incorporating nutrition content into medical education include financial constraints and determining how to teach and who should teach nutrition, but registered dietitians (RDs) and dietetic interns are in position to advocate for nutrition inclusion in care teams and promote nutrition training in medicine. Methods: Nutrition curriculum was developed after surveying nutrition professionals and trainees and incorporated into University of Minnesota medical student site visits to the Minneapolis VA Medical Center. Curriculum included an overview of RD training, the difference between RDs and nutritionists, areas of nutrition specialization, the role of RDs in various care settings, physician attitudes towards ancillary health care professionals affecting patient attitudes, and an overview of nutrition assessments. A diet history and malnutrition assessment nutrition-focused physical exam training were included as interactive activities. Fifty-two students were instructed by a dietetic intern in one of twelve groups of 2–5 during 30–60 minute sessions. Medical students provided feedback on what was learned, what could be applied in future practice, and comments about the training. Results: Medical students requested additional nutrition training time and reported awareness of nutrition considerations and RDs in clinical practice, intention to work with RDs, and intention to utilize techniques for diet histories and nutrition-focused physical exams in future assessments. Future work will address program sustainability and efficacy of training videos. Conclusions: Registered dietitians and dietetic interns are often in proximity to medical students and could teach nutrition assessments and interdisciplinary collaborations. Providing future physicians the knowledge, skills, and confidence to appropriately incorporate nutrition into practice while collaborating with RDs could positively impact health care and patient care outcomes. Funding Sources: N/A